Legal approach to the concept of Psychosocial Risks at work:: Algerian legislation as a subject of study - Belaredj, Mohamed Amine; Belabdoune, Aouad (Journal of Human Sciences, 2023)
Psychosocial risks are a fundamental and central issue in the world of work, and among the major challenges and bets facing states and societies. Algeria, like other countries, has not been immune to these emerging risks, which have become threatening and targeting employees in the workplace. Despite the high level of this category of occupational risks, the Algerian legislative system has not responded to these threats, which have been accompanied by a legal vacuum that has been the victim of the working class, which suffers in silence. In the absence of a special legal system to deal with these emerging threats, this study aimed to highlight the legislative mechanisms and the means available and current to protect employees and protect them from psychosocial risks.